Application of K-Means Clustering to Monitoring the level of Fertilizer Usage in Rice Fields in Ngawi Regency - Iwan Ady Prabowo; Hendro Wijayanto; Sujud Aji Wantoro (STMIK Sinar Nusantara, 2022)
Fertilizer is a substance given to plants that could be food for plants. Fertilizer itself divided into two types, that is inorganic fertilizers and organic fertilizer. Fertilizer is very important to the needs of farmers, especially farmers. Therefore fertilizer needs should be able to in monitoring in order not to occur lack. The purpose of this study is a grouping of the use of fertilizer in every town in the districts of Ngawi with k-Means algorithm. The formulation of the problem to overcome is how to apply the method of k-means algorithm to categorize fertilizer needs in every town in the Ngawi. K-means is clustering algorithm where one object can be in group based on data similarities. Clustering results K-means Clustering is seen in the first group high (Cluster 1) contains 6, In the second group medium (Cluster 2) contains 2 sub-districts, while in the third group low (cluster 3rd) contains 11 sub-districts.